Rare and unusual case of polyarteritis nodosa involving the gastrointestinal tract leading to bowel gangrene - Jagwani A.V.; Fathi N.Q.; Jailani R.F.; Zakaria A.D. (BMJ Publishing Group, 2024)
Indexed by SCOPUS